Socialization of Rhodamine B Dye Content in Liptint Sold in Lubuk Pakam Which is Analyzed Using UV-Vis Spectrophotometry (JURNAL PENGMAS KESTRA (JPK), 2023)
Rhodamine B is a synthetic dye that is always used to color paper, textiles or ink. The use of rhodamine B is very unsafe for physical fitness and health. When applied without an agent in the body, Rhodamine B irritates the respiratory tract and can cause cancer and liver damage. Even though it has negative effects, this dye is still widely used by irresponsible individuals to make a profit, especially in food processing and cosmetics. Objective: This community service is carried out with the aim of educating the public about the dangers of rhodamine for our bodies, as well as finding out the Rhodamine B content in lipsticks distributed in Lubuk Pakam, where lipstick is one of the cosmetics most widely used by the public, especially women. Method: The method used is socialization by providing direct outreach to the community, especially to mothers and teenagers about the dyes in lip tint which refer to the research results. Qualitative analysis of rhodamine B was carried out using TLC with the mobile phases of ethyl acetate, methanol and ammonia (45 :25:30), while quantitative analysis was carried out in the determination using UV-VIS spectrophotometry at 545 nm. The strategy used in providing knowledge about the dangers of dyes in cosmetics is by giving direct lectures about the various kinds of dyes used in cosmetics, the potential dangers that will arise if cosmetics with excessive dyes are used along with the characteristics of cosmetics with dyes and It is hoped that the public can avoid cosmetics that are indicated to use dyes and get safe cosmetic solutions using natural dyes.